Magnetic nanoparticles are highly toxic to chloroquine-resistant Plasmodium falciparum, dengue virus (DEN-2), and their mosquito vectors - Murugan, Kadarkarai; Wei, Jiang; Alsalhi, Mohamad Saleh; Nicoletti, Marcello; Paulpandi, Manickam; Samidoss, Christina Mary; Dinesh, Devakumar; Chandramohan, Balamurugan; Paneerselvam, Chellasamy; Subramaniam, Jayapal; Vadivalagan, Chithravel; Hui, Wei; et al. (Springer, 2017)
SURESH KUMAR SUBBIAH (A04156) / / / Kadarkarai Murugan,Jiang Wei,Mohamad Saleh Alsalhi,Marcello Nicoletti,Manickam Paulpandi,Christina Mary Samidoss,Devakumar Dinesh,Balamurugan Chandramohan,Chellasamy Paneerselvam,Jayapal Subramaniam,Chithravel Vadival